PHP 8 quick scripting reference : a pocket guide to PHP web scripting - Olsson, Mikael (Web programmer) (Apress, 2021)
This pocket reference has been updated with the new PHP 8 release. It is a condensed, code-rich scripting and syntax handbook for the PHP scripting language. You won't find any technical jargon, bloated samples, drawn-out history lessons or witty stories in this book. What you will find is a web scripting language reference that is concise, to the point, and highly accessible. The book is packed with useful information and is a must-have for any PHP programmer or web developer. In it, you will find a concise reference to the PHP 8 scripting language syntax. It includes short, simple, and focused code examples; a well-laid-out table of contents; and a comprehensive index allowing easy review. PHP 8 Quick Scripting Reference presents the essentials of PHP in a well-organized format, including new features in PHP 8 such as the just in time (JIT) compiler, union types, nullsafe operator, null coalescing assignment operator, match expressions, named arguments, throw expressions, static return type, non-capturing catches, reclassified engine warnings and constructor property promotion. You will: Discover what is new in PHP 8 and how to get started with it Work with variables, operators, strings, arrays, conditionals, loops, and other constructs Group and reuse code with functions, methods, and namespaces Use object-oriented features such as classes, inheritance, abstract classes, and interfaces Import files and retrieve user data Make use of type declarations and type conversions Test variables, create references, and use overloading methods Store user data with cookies and sessions Deal with errors through error handling, exception handling, and assertions.